Controlling for Lagged Stock Price Responses in Pricing Regressions: An Application to the Pricing of Cash Flows and Accruals - Pfeiffer, Ray J.; Elgers, Pieter T. (Journal of Accounting Research, 1999)
Ray J. Pfeiffer, Jr., Pieter T. Elgers, Controlling for Lagged Stock Price Responses in Pricing Regressions: An Application to the Pricing of Cash Flows and Accruals, Journal of Accounting Research, Vol. 37, No. 1 (Spring, 1999), pp. 239-247